Cranial Vault Deformation and Its Association with Mandibular Deviation in Patients with Facial Asymmetry: A CT-Based Study - Mayuko Nishimura; Chie Tachiki; Taiki Morikawa; Dai Ariizumi; Satoru Matsunaga; Keisuke Sugahara; Yasuo Aihara; Akira Watanabe; Akira Katakura; Takakazu Kawamata; Yasushi Nishii (Diagnostics)
Background/Objectives: Facial asymmetry is known to cause not only deformities in the facial skeleton but also alterations in the cranial vault. However, limited research has explored the association between mandibular asymmetry and cranial vault deformation. This study aimed to evaluate the three-dimensional craniofacial morphology, including the cranial vault, in patients with skeletal mandibular prognathism using computed tomography (CT) imaging. Methods: Patients were classified into two groups: those with facial asymmetry (ANB ≤ 0°, Menton deviation ≥ 4 mm) and those without (ANB ≤ 0°, Menton deviation < 3 mm). Reference planes were established in three orthogonal directions, and distances from anatomical landmarks on the maxilla and mandible to each reference plane were measured. Additionally, the cranial vault was segmented into four regions, and the volume of each section was calculated. Results: Compared with the symmetric group, the asymmetric group exhibited significant lateral displacement in the maxilla and both anteroposterior and lateral displacements in the mandible. Furthermore, a significant difference in the posterior cranial vault volume between the left and right sides was observed in the asymmetric group. A moderate positive correlation (r = 0.543, p = 0.045) was also found between the direction of mandibular deviation and the direction of posterior cranial vault deformation. Conclusions: A moderate positive correlation (r = 0.543, p = 0.045) was observed between mandibular deviation and posterior cranial vault asymmetry. These findings may suggest that the cranial vault morphology may influence facial asymmetry, and it may serve as one of the considerations for discussing the necessity of early intervention for cranial vault deformity during infancy.